Development of Electrochemical Oscillation Method for Identification of Prunus persica, Prunus davidiana, and Prunus armeniaca Nuts - Yan, Shuai; Yue, Yinzi; Su, Lianlin; Hao, Min; Wang, Xiaopeng; Zuo, Ting (Frontiers in Chemistry, 2020)
In this work, an electrochemical oscillation system (EOS) has been developed using Belousov-Zhabotinskii (B-Z) reaction. The effect of combination of each reagent, reaction temperature and stirring speed on induction period, oscillating period and oscillating life were optimized. The nuts of Prunus persica, Prunus davidiana and Prunus armeniaca have been widely used for medical purpose. The proposed EOS was then used for identification of Prunus persica, Prunus davidiana and Prunus armeniaca. Three nuts exhibited very different electrochemical oscillation profiles. The dendrogram was divided into three main principal infrageneric clades. Each cluster only contains one species, suggesting that no outlier was observed in this study. Based on the above results, we proposed a simple method for herbal medicines identification.